Targeting the Sonic Hedgehog Signaling Pathway: Review of Smoothened and GLI Inhibitors - Rimkus, Tadas K. (Cancers (Basel), 2016)
The sonic hedgehog (Shh) signaling pathway is a major regulator of cell differentiation, cell proliferation, and tissue polarity. Aberrant activation of the Shh pathway has been shown in a variety of human cancers, including, basal cell carcinoma, malignant gliomas, medulloblastoma, leukemias, and cancers of the breast, lung, pancreas, and prostate. Tumorigenesis, tumor progression and therapeutic response have all been shown to be impacted by the Shh signaling pathway. Downstream effectors of the Shh pathway include smoothened (SMO) and glioma-associated oncogene homolog (GLI) family of zinc finger transcription factors. Both are regarded as important targets for cancer therapeutics. While most efforts have been devoted towards pharmacologically targeting SMO, developing GLI-targeted approach has its merit because of the fact that GLI proteins can be activated by both Shh ligand-dependent and -independent mechanisms. To date, two SMO inhibitors (LDE225/Sonidegib and GDC-0449/Vismodegib) have received FDA approval for treating basal cell carcinoma while many clinical trials are being conducted to evaluate the efficacy of this exciting class of targeted therapy in a variety of cancers. In this review, we provide an overview of the biology of the Shh pathway and then detail the current landscape of the Shh-SMO-GLI pathway inhibitors including those in preclinical studies and clinical trials.